Craniofacial morphology in males with 46,XX chromosomal constitution - Šćepan Ivana; Glišić Branislav; Babić Marko; Nikolić Zorana; Đorđević Dušan (Serbian Medical Society - Dental Section, Belgrade, 2003)
The aim of this investigation was to assess the craniofacial morphology of five male individuals with 46,XX chromosomal constitution, and to compare them with normal male individuals (46,XY) and normal female participates (46,XX). The investigation was carried out on the lateral cephalomestic radiographs of five male individuals with sex reverse syndrome (46,XX chromosomal constitution), 62 normal female (46,XX) and 31 normal male (46,XY chromosomal constitution) participants. The following angular variables were measured: SNA, SNB, ANB, SN/SpP, SN/MP and SpP/MP. For each variable the mean value and standard deviation were calculated. The Student t-test was used to compare the result obtained between the group of patients with sex reverse syndrome and group of normal male, as well as of normal female participants. The male individuals with 46, XX chromosomal constitution showed slight bimaxillary retrognathism, and class III sagittal jaw relationship. Due to decreased inclination of the upper jaw to the anterior cranial base, the angle of vertical jaw relationship slightly increased in the group of patients with sex reverse syndrome, compared to normal male and female participants.